A comparison of stomatal conductance responses to blue and red light between C3 and C4 photosynthetic species in three phylogenetically-controlled experiments - Bernardo, Emmanuel L.; Sales, Cristina Rodrigues Gabriel; Cubas, Lucía Arce; Vath, Richard L.; Kromdijk, Johannes (Frontiers in Plant Science, 2023)
C4 photosynthesis is an adaptation that has independently evolved at least 66 times in angiosperms. C4 plants, unlike their C3 ancestral, have a carbon concentrating mechanism which suppresses photorespiration, often resulting in faster photosynthetic rates, higher yields, and enhanced water use efficiency. Moreover, the presence of C4 photosynthesis greatly alters the relation between CO2 assimilation and stomatal conductance. Previous papers have suggested that the adjustment involves a decrease in stomatal density. Here, we tested if C4 species also have differing stomatal responses to environmental cues, to accommodate the modified CO2 assimilation patterns compared to C3 species. To test this hypothesis, responses to blue and red-light were analysed in three phylogenetically linked pairs of C3 and C4 species from the Cleomaceae (Gynandropsis and Tarenaya), Flaveria, and Alloteropsis, that use either C3 or C4 photosynthesis. The results showed strongly decreased sensitivity to blue light in C4 dicots, compared to their C3 counterparts, which exhibited significant blue light responses. In contrast, in C3 and C4 subspecies of the monocot A. semialata, the blue light response was observed regardless of photosynthetic type. Further, the quantitative red-light response varied across species, but the presence or absence of a significant stomatal red-light response was not directly associated with differences in photosynthetic pathway. Interestingly, stomatal density and morphology patterns observed across the three comparisons were also not consistent with patterns commonly asserted for C3 and C4 species. Altogether, the strong prevalence of species-specific effects clearly emphasizes the importance of phylogenetic controls in comparisons between C3 and C4 photosynthetic pathways.